2018
DOI: 10.21010/ajtcamv15i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hypoglycemic Effects of Watercress (Nasturtium Officinale) Extracts in Diabetic Rats

Abstract: Background: Watercress is a semi-aquatic plant used in traditional medicine to treat various ailments, such as flu, cough, avitaminosis, and anorexia; it is also used as a diuretic and for hypoglycemia treatment in diabetes. In this study, we report the antioxidant and hypoglycemic activity of orally administered aqueous (WAQE), acetonic (WAE), and alcoholic (WOHE) watercress extracts. The effect of subchronic administration of watercress extracts on oxidative stress was also studied. Materials and Methods: WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
4
1
2
Order By: Relevance
“…Our results showed that EENO supplementation in the intervention group did not affect the activity of this enzyme. Contrary to the finding of the current work, in some animal models of hypercholesterolemia and diabetes in rats, EENO increased the activity of GPx [ 34 , 35 ]. This difference can be due to the difference between animal models with the clinical trials.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results showed that EENO supplementation in the intervention group did not affect the activity of this enzyme. Contrary to the finding of the current work, in some animal models of hypercholesterolemia and diabetes in rats, EENO increased the activity of GPx [ 34 , 35 ]. This difference can be due to the difference between animal models with the clinical trials.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings confirm the previous results that showed EENO increased the SOD activity in hypercholesterolaemic rats [ 34 ]. Our results also are consistent with the previous study that reported EENO increased the activity of SOD in diabetic rats [ 35 ]. Contrary to the results of the present study, Clemente and coworkers, in a human clinical trial on the antioxidants effect of EENO supplementation in people with a physical disability, showed that EENO fails to increase the SOD activity [ 33 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Fenton-Navarro et al showed that the hypoglycemic effect of aqueous WC extract during acute mode was 76.6% more than that of insulin, and once aqueous WC was used in the chronic period, the levels of glucose reached the normal range during the third week to the eighth week of the experiment. [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Oksidatif stress, diyabet etiyolojisinde önemli bir rol oynar, mikrovasküler ve makrovasküler komplikasyonlara, katarakta, nefropatiye ve nörolojik bozukluklara neden olabilmektedir. Ayrıca diyabetli hastaların antioksidan savunma sistemi zayıflamış olup, serbest radikaller tarafından doku hasarı riski artmaktadır [6]. Hipergliseminin yanı sıra, diabetes mellitus hastalığında plazma lipid seviyeleri genellikle yükselmekte olup koroner kalp hastalığı için bir risk faktörü oluşturmaktadır.…”
Section: Introductionunclassified